Transformation of Administration and Government Bureaucracy in Efforts to Improve the Quality of Public Services - Komang Suryaningsih; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The transformation of government administration and bureaucracy is a strategic step to improve the quality of public services in the modern era. This study examines the government's efforts to create governance that is more effective, efficient, transparent, and accountable through technological innovation, regulatory simplification, and decentralization. The implementation of e-government and the enhancement of human resource capacity are critical elements in realizing public services that are responsive to societal needs. This transformation not only serves to enhance administrative efficiency but also strengthens public trust in the government.